Toxic effects of plastic on human health and environment : A consequences of health risk assessment in Bangladesh - Proshad, Ram; Kormoker, Tapos; Islam, Md. Saiful; Haque, Mohammad Asadul; Rahman, Md. Mahfuzur; Mithu, Md. Mahabubur Rahman (International Journal of Health, 2017)
Plastics are used widely everywhere in our life and without plastic, modern civilization would indeed look very diverse. This study focuses on the toxic effects of plastic on human health and environment and possible consequences of health risk assessment in Bangladesh. Plastics are essential materials in modern civilization, and many products manufactured from plastics and in numerous cases, they promote risks to human health and the environment. Plastics are contained many chemical and hazardous substances such as Bisphenol A (BPA), thalates, antiminitroxide, brominated flame retardants, and poly- fluorinated chemicals etc. which are a serious risk factor for human health and environment. Plastics are being used by Bangladeshi people without knowing the toxic effects of plastic on human health and environment. Different human health problems like irritation in the eye, vision failure, breathing difficulties, respiratory problems, liver dysfunction, cancers, skin diseases, lungs problems, headache, dizziness, birth effect, reproductive, cardiovascular, genotoxic, and gastrointestinal causes for using toxic plastics. Plastics occur serious environment pollution such as soil pollution, water pollution, and air pollution. Application of proper rules and regulations for the production and use of plastics can reduce toxic effects of plastics on human health and environment.